Effect of Outreach on Financial Sustainability and Profitability of Saving and Credit Cooperatives in Eastern Ethiopia - Yitayaw, Mekonnen (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2020)
This study scrutinized the effect of outreach on financial sustainability and profitability of SACCOs in Eastern Ethiopia using balanced panel data from 33 SACCOs over the period of 2017-2019. Quantitative approach and explanatory design were employed to realize the stated objective. This study used secondary data sources, mainly audited financial statement of the SACCOs, in the study period. The analysis revealed that SACCOs in Eastern Ethiopia are profitable but not financially sustainable. Random effect model results show that gross loan to asset ratio, yield on gross loan portfolio, managerial and operational efficiency has statistically significant and positive effect on the financial sustainability of SACCOs, while average loan size has statistically significant but negative effect. Likewise, gross loan to asset ratio, managerial efficiency, and average loan size has statistically significant and positive effect on the profitability of SACCOs in Eastern Ethiopia. However, the portion of women borrowers and number of active borrowers has statistically significant but negative effect on the profitability of the SACCOs in the study area. Finally, the study suggests that increasing the number of borrowing clients and sales volume (loan portfolio) could benefit SACCOs in Eastern Ethiopia from economics of scale.